What matters for vegetation regeneration in Brazilian subtropical grasslands: seeders or resprouters? - Fidelis, Alessandra [UNESP]; Rodrigues, Cassy Anne [UNESP]; Dairel, Mariana [UNESP]; Blanco, Carolina C.; Pillar, Valério D.; Pfadenhauer, Jörg (Elsevier, 2021)
Fire is an important ecological and evolutionary factor affecting plant communities worldwide. After fire, plants can resprout or germinate and systems may differ according to their post-fire regeneration strategies. Therefore, the main aim of this study was to analyze the most important regeneration strategies in Brazilian subtropical grasslands. Moreover, we point out differences in seedlings and resprouts between burned and mowed plots, in order to detect differences in community response to different types of disturbance. We analyzed seven pairs of plots (burned and mowed) in two sites with different fire histories: FB – frequently burned grasslands, and E – exclusion of fire for six years. After treatments, vegetation was described and seedlings and resprouts were sampled. Plants were later grouped in species groups for statistical analyses. Less than 20% of established plants came from seedlings and only three species were obligate seeders. Most species resprouted after treatments. Number of seedlings and resprouts did not show significant differences between treatments in each site. However, a higher number of species with seedlings was observed in site FB. More new species with seedlings established in burned than mowed plots in site FB. Seedlings of forbs recruited more in burned than in mowed plots. Resprouter was the most important strategy for all studied species groups, particularly for graminoids. Our results show the importance of vegetative regeneration in the studied subtropical grasslands, independently of disturbance, and the importance of fire for the establishment of new species, maintaining thus, plant diversity.
Keywords: Brazilian subtropical grasslands: Fire; Mowing; Obligate seeders; Regeneration strategies